2015
DOI: 10.1177/0961203314566636
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D receptor (VDR) gene polymorphisms and systemic lupus erythematosus in Portuguese patients

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown origin, in which both genetic and environmental factors are involved. One such environmental factor is vitamin D, a vital hormone that plays a specific function in the immune system homeostasis, acting through a nuclear receptor (VDR) expressed in all immune cells. Several polymorphisms of the gene that encodes this receptor have been described. Though inconsistently, these polymorphisms have been associated with clinical manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 42 publications
(62 reference statements)
3
63
1
1
Order By: Relevance
“…For this reason, genetic variation in the VDR gene changing its binding affinity, activity or protein levels may influence the immunological efficiency of vitamin D. In addition, in vitro and knock-out mice experiments have linked VDR to the resistance to Leishmania major infection 32 . Indeed, genetic variants in the VDR gene have also been associated with an increased risk of chronic chagasic cardiomyopathy 51 , malaria severity 52 , tuberculosis 53 , and some autoimmune disorders 54, 55 . Our results showed that the four VDR polymorphisms display similar frequencies across the non-infected, asymptomatic, and symptomatic dog groups (Table 3), and no genetic association between these SNPs and disease/infection status were observed (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, genetic variation in the VDR gene changing its binding affinity, activity or protein levels may influence the immunological efficiency of vitamin D. In addition, in vitro and knock-out mice experiments have linked VDR to the resistance to Leishmania major infection 32 . Indeed, genetic variants in the VDR gene have also been associated with an increased risk of chronic chagasic cardiomyopathy 51 , malaria severity 52 , tuberculosis 53 , and some autoimmune disorders 54, 55 . Our results showed that the four VDR polymorphisms display similar frequencies across the non-infected, asymptomatic, and symptomatic dog groups (Table 3), and no genetic association between these SNPs and disease/infection status were observed (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Ozaki et al [31] reported BsmI polymorphisms in 58 Japanese SLE patients; their findings revealed that the BB genotype might trigger the development of lupus and the bb genotype was associated with lupus nephritis. Carvalho et al [32] suggested a possible role of VDR gene polymorphisms in Portuguese patients with SLE as a positive association was found between VDR gene variants and lupus severity (chronic damage).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that 1,25(OH) 2 D 3 could regulate the expression of many apoptosis factors or mediators and directly induce apoptosis through the activation of Caspase, which had been proved that it could reduce the immunostimulatory effects of the SLE [24,25]. Carvalho et al had illustrated vitamin D, acting through VDR expressed in all immune cells, played an important role in the immune system homeostasis, and VDR polymorphisms and SLE had positive association [26]. In addition, some immunosuppressive effects were mediated by the interaction of hormone and nuclear receptor, and it had found that VDR could regulate gene expressions of sensitive tissues in vitamin D [27], which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%